Volatiles of fungal cultivars act as cues for host-selection in the fungus-farming ambrosia beetle Xylosandrus germanus - Gugliuzzo, Antonio; Kreuzwieser, Jürgen; Ranger, Christopher M.; Tropea Garzia, Giovanna; Biondi, Antonio; Biedermann, Peter H. W. (Frontiers in Microbiology, 2023)
Many wood-boring insects use aggregation pheromones during mass colonization of host trees. Bark beetles (Curculionidae: Scolytinae) are a model system, but much less is known about the role of semiochemicals during host selection by ambrosia beetles. As an ecological clade within the bark beetles, ambrosia beetles are obligately dependent on fungal mutualists for their sole source of nutrition. Mass colonization of trees growing in horticultural settings by exotic ambrosia beetles can occur, but aggregation cues have remained enigmatic. To elucidate this mechanism, we first characterized the fungal associates of the exotic, mass-aggregating ambrosia beetle Xylosandrus germanus in Southern Germany. Still-air olfactometer bioassays documented the attraction of X. germanus to its primary nutritional mutualist Ambrosiella grosmanniae and to a lesser extent another common fungal isolate (Acremonium sp.). During two-choice bioassays, X. germanus was preferentially attracted to branch sections (i.e., bolts) that were either pre-colonized by conspecifics or pre-inoculated with A. grosmanniae. Subsequent analyses identified microbial volatile organic compounds (MVOCs) that could potentially function as aggregation pheromones for X. germanus. To our knowledge, this is the first evidence for fungal volatiles as attractive cues during host selection by X. germanus. Adaptive benefits of responding to fungal cues associated with an infestation of conspecifics could be a function of locating a suitable substrate for cultivating fungal symbionts and/or increasing the likelihood of mating opportunities with the flightless males. However, this requires solutions for evolutionary conflict arising due to potential mixing of vertically transmitted and horizontally acquired symbiont strains, which are discussed.